1996
DOI: 10.1046/j.1365-2249.1996.d01-869.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to double-stranded (ds)DNA immunoprecipitate 18S ribosomal RNA by virtue of their interaction with ribosomal protein S1 and suppress in vitro protein synthesis

Abstract: SUMMARYWe report that four systemic lupus erythematosus (SLE) patient sera containing anti-dsDNA antibodies, three affinity-purified anti-dsDNA IgG, and a human anti-dsDNA MoAb (33.H11) immunoprecipitate 18S ribosomal RNA from DNase-treated 32 P-labelled MOLT4 cell extract. This 18S RNA precipitation was inhibited completely by preincubating 33.H11 with calf thymus dsDNA or the recombinant human ribosomal protein S1, which was reported to cross-react with anti-dsDNA antibodies (J Immunol 1996; 156:1668-75). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…To our surprise, it has been shown that the cDNA library purchased commercially, which was used to select a cDNA encoding the ribosomal S1 protein, contained a cDNA encoding a ribosomal S1 protein from the bacterial species L. lactis (26). Nonetheless, a human analogue of these proteins appears to exist on the small ribosomal subunit, since anti-dsDNA antibodies immunoprecipitate 18S ribosomal RNA and suppress in vitro translation (19). In light of our previous observations demonstrating the reactivity of anti-dsDNA antibodies to ribosomal S1 protein (25) we utilized rabbit polyclonal antibodies toward the ribosomal S1 protein as a probe to identify analogous antigenically and functionally related proteins from eukaryotic cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our surprise, it has been shown that the cDNA library purchased commercially, which was used to select a cDNA encoding the ribosomal S1 protein, contained a cDNA encoding a ribosomal S1 protein from the bacterial species L. lactis (26). Nonetheless, a human analogue of these proteins appears to exist on the small ribosomal subunit, since anti-dsDNA antibodies immunoprecipitate 18S ribosomal RNA and suppress in vitro translation (19). In light of our previous observations demonstrating the reactivity of anti-dsDNA antibodies to ribosomal S1 protein (25) we utilized rabbit polyclonal antibodies toward the ribosomal S1 protein as a probe to identify analogous antigenically and functionally related proteins from eukaryotic cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then loaded onto an anion-exchange DE-52 column equilibrated with 0.01 M phosphate buffer, pH 7.2 (Whatman Biosystems Ltd., Maidstone, Kent, UK), and IgG was eluted with the same phosphate buffer. Purified anti-dsDNA IgG was eluted from DNA cellulose columns (Sigma, St. Louis, MO) as described previously (19). Nine affinity-purified anti-dsDNA Abs, three human monoclonal anti-dsDNA Abs, two affinity-purified anti-ribosomal P Abs, and Cohn fraction II IgG (Sigma) were used in translation assays (19).…”
Section: Preparation Of Lupus Anti-dsdna Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 33.H11 inhibited in vitro translation of globulin mRNA, which was enhanced when the reticulocyte lysate was treated with DNAse. From these data it might be speculated that suppression of protein synthesis could be regarded as a pathogenic mechanism of anti-dsDNA antibodies, since it had previously been shown that some anti-dsDNA antibodies were able to penetrate living cells in culture [67,68]. The different biological activities of monoclonal anti-dsDNA antibodies obtained from one patient give rise to the hypothesis that at least one possible mechanism leading to a specific organ targeting by anti-dsDNA antibodies in SLE could be due to a cross-reactivity of anti-dsDNA antibody clones with organ-specific antigens.…”
Section: Anti-dsdna-and Immune-complexmediated Organ Damagesmentioning
confidence: 99%